Sapere aude – v. 10, n. 19, p. 7-9, jan./jun. 2019 – ISSN: 2177-6342 - PUC Minas, Departamento de Filosofia (Sapere Aude, 2019)
SAPERE AUDE DOSSIÊ: PAIXÕES NA FILOSOFIA ANTIGA Sapere aude – v. 10, n. 19, p. 7-9, jan./jun. 2019 – ISSN: 2177-6342